Adiposity is associated with a higher number of thyroid nodules and worse fine-needle aspiration outcomes - Elpida Demetriou; Aliki Economides; Maria Fokou; Demetris Lamnisos; Stavroula A Paschou; Panagiotis Papageorgis; Panayiotis A Economides (European Thyroid Journal)
Background: Adiposity may be associated with thyroid nodularity. However, its impact on the number of nodules and the risk of malignancy is unclear. Aim: To evaluate the impact of adiposity on thyroid nodules using body mass index (BMI), ultrasonographic (US) data and cytological data. Methods: A retrospective cohort study of 310 patients with thyroid nodules was performed. Patients were categorized based on their BMI, and grayscale US data and fine-needle aspiration cytology results were evaluated. Results: Patients with BMI ≥ 25 kg/m2 were found to have a higher number of thyroid nodules compared to those with BMI < 25 kg/m2 (4.25 ± 2.42 vs 3.66 ± 1.93) (P value = 0.05). Patients with BMI ≥ 25 kg/m2 had more suspicious and malignant cytology than those with BMI < 25 kg/m2 (P value = 0.029). Patients with BMI ≥ 25 kg/m2 had more nodules with intermediate and high suspicion sonographic patterns. However, this did not reach statistical significance. Conclusion: Overweight and obese patients have a trend for more thyroid nodules and have a higher risk of being diagnosed with thyroid malignancy.